DYNAMOMETRY INDICATORS OF CHILDREN IN PREPARATORY GROUPS OF PRESCHOOL EDUCATIONAL INSTITUTIONS IN KEMEROVO - Селиверстов, Илья Александрович; Перевощикова, Нина Константиновна; Дракина, Светлана Альбертовна; Анисимова, Анна Владимировна; Кабанова, Кристина Витальевна; Черных, Наталья Степановна (Mother and Baby in Kuzbass, 2022)
The aim of the investigation is to study the possibilities of dynamometry indicators for the assessment of muscle strength, power endurance and physical activity of children in preparatory groups of preschool educational institutions in Kemerovo. Materials and methods. We investigated 392 children studying on the bases of Kemerovo preschool educational institutions, from them: boys 6 years – 118 (mean age – 6 years 6 months ± 2,93 months), 7 years – 86 (mean age – 7 years 2 months ± 2,01 months), girls 6 years – 112 (mean age – 6 years 6 months ± 2,67 months), 7 years – 76 (mean age – 7 years 2 months ± 1,98 months). All children were measured for physiometric indices of muscular strength, power endurance using the technique of wrist dynamometry. Results and their discussion. The basis for the health of children of different ages is a rational daily routine and its components, in this connection we assessed the physical activity of children during the day at the time of study in preschool preparatory groups by means of double dynamometry: in the morning (8 h a.m.) and in the evening (6 h p.m.). According to the data obtained, more than half of the children had insufficient physical activity during the day, as evidenced by the absence of changes in the dynamometry indices and their decrease. The difference in the muscular strength parameters of the preparatory group of children aged 6 and 7 years was higher for girls and amounted to 1.01 kg (16.03 %) vs. 0.44 kg (6.03 %) for boys. Parameters of relative strength and strength index among girls were characterized by higher values. Determination of strength endurance showed that girls demonstrated a more pronounced increase in reserves to the ability to create a prolonged muscular effort. Conclusion. The results of the investigation revealed a high incidence of signs of irrational regime and maladaptive disorders in relation to physical activity. The children of preparatory preschool groups were characterized by low indices of strength endurance and insufficient adaptation to physical activity.